Slum toponymy in Nairobi: A cultural arena for socio-political justice and symbolic resistance - Wanjiru, Melissa; Matsubara, Kosuke (International Planning History Society Proceedings, 2016)
Slum dwellers in Nairobi, despite making up half of the city’s population , are a socially, politically and economically marginalised group. There are an estimated 134 slums which occupy about 1% of the city area . Much research has been done on the challenges facing slum dwellers with an aim to improve their living conditions. This study aims to contribute to that effort by analysing how the names of places (toponymy) within slums, can be used to explain the challenges of these settlements from the vantage point of the namers – the residents themselves. The name then becomes an illuminating social code as regards the spatial organization of the slums . Typically, slums in Nairobi are named after the original settlers (Mukuru -kwa Reuben and kwa Njenga), geographical conditions (Kibera, Mashimoni), other places (Beirut, Kosovo and Vietnam) or past local and global events (Soweto Uprising in South Africa). Other names are a blend of one or more things or could mean different things at the same time. For instance Kosovo, Vietnam and Soweto, could be references to the wars and uprising and not the locations themselves. These examples evidence the inclination of slum toponymy towards places or events associated with social-political struggles. It is on this premise that we look at the symbology behind the names, what they communicate about the lives of the residents and their resilience in the face of many socio-political and economic challenges. In this study we will take Kibera as a specific case. It is the largest slum in Kenya and Africa. Data on Kibera was obtained through: archival research, a Focused Group Discussion held with the Nubian Council of elders, and field surveys in September 2015. Analysis was done through toponymic layering to show how names have evolved along a time-space continuum. These toponymic layers were further analysed along ethnic, political, geographical and historical axes to understand their meanings and implications on space. The study showcases the cultural and social resistance and resilience of urban slum dwellers in Nairobi. Toponymic resistance (warfare) is seen through: use of global names associated with conflict to highlight their plight, refusal to use names imposed by government, or the use of ethnic names in order to mark spatial territories. All these struggles are embedded within the spatial toponymic framework of Nairobi slums.